(3GdecGSH hGdeYGjT heG jJYdb HPdcs - (3gGOj Hf YHGS Hf Ydj GHf cGTa GdZWGA, J (B1360(3g` (B1941(3es ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdPj LYd GdCQV PdhdG hLYd ajgG eJGYG heYGTG (B... (3ebOeI ajgG aUhd GdChd aj PcQ eG jOd Ydi aVd GdcSH ef GdCNHGQ JHQcG hJjefGs
(3BNQgG (B:s
(3BNQgG(B: (3GdQHGY GdJUQa GdeZjQ ddUhQI hdG dRhe Ydi GdEHGMI hYdi Gdbhd HGdedc aaj GddRhe hLgGJ HfjGf Ydi LQjGf GSJUMGH LhGR (B.... (3Ke Ef LhGR GdQLhY aj GdeYGTGJ djS fXjQ GdfSN aj GdYbhOs
(3jHOh CfgG eShOI GdeDda deG ajgG cTJ hTWH hJYOjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B8: 58s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis